Analysis of the connection between contract and reality: A review of Kant’s school of thought regarding the basis of contract credibility - Narges Khaleghipoor; Davood Nasiriyan-e-Najafabadi (مطالعات فقه و حقوق اسلامی)
The nature of a contract is constructional and it is set by the human will, making it distinguishable from social and experimental realities that are formed in the real world. the question here is the extent of the connection between contract and reality. Is it a pure function of reality? Furthermore, we’ll explore the existence and continuation of a contract and how it is affected by external realities in Kant’s volitional school of thought. How effective is the role of the human will in the conclusion of a contract? What are the consequences of pure voluntarism? From the point of view of voluntarists, the contract takes priority rather than reality, and the point of origin for contracts is the human will, and socio-experimental reality cannot be considered the basis of a contract. Equity and the La-Haraj rule are not applicable in this school of thought. In addition to maintaining the integrity of the contract and ensuring its survival under any circumstances and in any location, Pure voluntarism exposes the solidity and Jamud present in contracts. In this school of thought, the lifecycle of the contract is a pure function of the will of its contractors and the human willretains its creative power and is not considered an instrumental aspect. According to this school of thought, this is where the benefits of the power of reasoning and human will prove important, and the principle of voluntarism plays an infrastructural role in the conclusion of a contract. The transactional relationship between the parties requires an adjustment of the pure voluntarism school of thought, to account for socio-experimental reality as well. Moderate positivism claims that a contract is influenced by reality, which adjusts the pure voluntarism school of thought in contracts.